2011
DOI: 10.1016/j.febslet.2011.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Redox control of iron regulatory protein 2 stability

Abstract: Edited by Stuart Ferguson Keywords:Iron metabolism Iron regulatory protein 2 Proteasome Oxidative stress Hypoxia a b s t r a c t Iron regulatory protein 2 (IRP2) is a critical switch for cellular and systemic iron homeostasis. In iron-deficient or hypoxic cells, IRP2 binds to mRNAs containing iron responsive elements (IREs) and regulates their expression. Iron promotes proteasomal degradation of IRP2 via the F-box protein FBXL5. Here, we explored the effects of oxygen and cellular redox status on IRP2 stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In these studies, the effects of hypoxia on binding of IRPs to IRE appear to be somewhat inconsistent or complex, or may be context-dependent including cell types and species, hypoxic oxygen percent, and duration and time points of hypoxic conditions (4042). Subsequent studies demonstrated that the relative involvement of IRP1 and IRP2 in the IRP-IRE regulatory system was determined by tissue oxygen levels and cellular redox states (43,44), and hypoxia stabilized and activated IRP2 through destabilization of FBXL5 and SKP1-CUL1 ubiquitin ligase protein complex (45,46) while hypoxia decreased IRP1 binding to IRE (43,47). Despite the induction of ferritin H mRNA by cobalt chloride in K562 cells, we found that ferritin H protein expression was strongly suppressed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the effects of hypoxia on binding of IRPs to IRE appear to be somewhat inconsistent or complex, or may be context-dependent including cell types and species, hypoxic oxygen percent, and duration and time points of hypoxic conditions (4042). Subsequent studies demonstrated that the relative involvement of IRP1 and IRP2 in the IRP-IRE regulatory system was determined by tissue oxygen levels and cellular redox states (43,44), and hypoxia stabilized and activated IRP2 through destabilization of FBXL5 and SKP1-CUL1 ubiquitin ligase protein complex (45,46) while hypoxia decreased IRP1 binding to IRE (43,47). Despite the induction of ferritin H mRNA by cobalt chloride in K562 cells, we found that ferritin H protein expression was strongly suppressed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As both mitochondria and TfR-mediated iron loading are simultaneously required for haeme synthesis, and the removal of both mitochondria and TfR are tightly regulated in erythroid cell maturation, these mechanisms are likely to be synchronized. A previous report found that ROS promoted translation of TfR thereby prolonging iron loading 45 . We propose that the continued presence of mitochondria in maturing erythroid cells is signalled to TfR through subtle ROS signalling, and is magnified by mtDNA mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Because they merely misregulated ferritin and TfR1 expression in the kidney and the brown fat, tissues with the highest abundance of IRP1, it was proposed that Irp2 dominates cellular iron metabolism in tissues, with Irp1 having an auxiliary physiological function (Meyron-Holtz et al, 2004a). In addition, Irp1 −/− (and Irp2 −/− ) mice did not exhibit any defects when challenged with turpentine to induce an inflammatory response (Viatte et al, 2009), despite the fact that IRPs are modulated in cultured cells by inflammatory reactive species such as H 2 O 2 and NO (Weiss et al, 1993; Pantopoulos and Hentze, 1995; Wang et al, 2005; Hausmann et al, 2011). …”
Section: Mouse Models With Ubiquitous Aberration In the Ire/irp Systemmentioning
confidence: 99%